Myte, fantasi og virkelighed - Davidsen, Ole (Religionsvidenskabeligt Tidsskrift, 1984)
On the basis of Freud’s article “Der Dichter und das Phantasieren”, it is possible to formulate a theory of myth as a distorted and elaborated manifestation of fantasies (wish-fulfilments) which have their source in ungratified wishes. It is the author’s hypothesis that “The Story of the Fall” is such a mythical manifestation, which builds a bridge between fantasy (Man is immortal) and reality (Man is mortal). Due to its semiotic structure of significance, the myth is able to adapt itself to reality without betraying the fantasy; and it is to presume that it is because of this very fact that the myth becomes a socially acceptable manifestation of the fantasy – in contrast to daydream, neurosis and phychosis.